Backpackers: The Next Generation? - Markward, Anne (Auckland University of Technology, 2008)
New Zealand has a well-established network of accommodations, transportation, and visitor activities developed specifically for backpackers. These tourists account for almost ten percent of the country’s international visitor expenditure. To date, the majority of backpacker research has focussed on the traditional market segment of student and youth travellers, though a few quantitative studies have also researched the needs and preferences of older travellers using hostels and backpackers’ accommodations. Though more than 50 percent of New Zealand’s international visitors are over age 40, few currently stay at this type of accommodation. Using New Zealand as a case study, this thesis explores, qualitatively, the perspectives of older backpackers: their self-perceptions, their travel motivations, their needs and expectations in accommodation. In addition, it examines the points of view of the owners of small, independent backpackers’ accommodations to gain their perspectives on hosting a multi-generational clientele and on what the implications might be of expanding this market. Key findings show that older travellers who use backpackers’ accommodations technically meet all Pearce’s (1990) original definitions of “backpacker” – they prefer budget accommodations, they are socially interactive, they travel independently and flexibly, they travel for longer holidays than do most, and they choose informal and participatory activities. However, these travellers reject the self-definition of “backpacker”, an impasse that presents a lexical challenge to both scholars and tourism marketers. The final section addresses the impacts and implications of “backpacker” nomenclature on baby boomer travellers, academia, and the backpacker industry at large.
Keywords: Backpackers; Baby boomers; Budget travel; Travel motivations; Self-perception; Qualitative